Mineral chemistry of the bimodal acid and basic dike swarms in the central part of the Dom Feliciano Belt, southern Brazil - CELI ZANON; RÔMULO MACHADO; RUY PAULO PHILIPP; UMBERTO G. CORDANI (Anais da Academia Brasileira de Ciências)
Abstract Basic acid dike swarms of Piratini and Pinheiro Machado areas in the Dom Feliciano belt are intrusive in the Pelotas Batholith. They were emplaced in a shallower crustal level than the batholith. U-Pb age of 560 Ma was obtained for them. We investigated in this paper the origin of these rocks (basic, intermediate, and acid) based on mineral chemistry (K-feldspar, plagioclase, clinopyroxene, amphibole and biotite), and on petrographic and field data. The decrease in TiO2 content from core to edge of clinopyroxene (diopside-augite) suggests that its crystallization occurred from a liquid sub-saturated in silica. The high values of mg# (0.71-0.94) of the core of amphibole crystals of intermediate dikes are comparable to the experimental data of amphiboles equilibrated with primitive basalt magmas. Biotite in the discriminant diagram (FeOtotal versus Al2O3) occupy the fields of the alkaline and peraluminous suites and at the boundary of the calc-alkaline and slightly peraluminous fields. The alkaline character in TAS diagram together with the plot of part of biotite samples in the field of rocks of the alkaline suite of Abdel-Rahman (1994) suggests connection with magmatism of mantle origin that was modified by processes of crustal contamination.